An Investigation into CIGS Thin-Films Solar Cell P2 Layer Scribing Depth and Width Using Different Laser Process Parameters - Dyi-Cheng Chen; Ming-Fei Chen; Ming-Ren Chen (Advances in Materials Science and Engineering)
This study will be about UV (355 nm) laser processing system as a carrier. It studied electrode insulated characteristic using laser direct forming for CIGS solar cell technology P2 layer of stainless steel. It explored the impact of this process on the way to stainless steel substrate P2 film sizes using its laser different focus position, energy density, and scanning velocities. According to the experiment results, the scribing results are straight line and larger width under minus leave perpendicularity and positive leave perpendicularity and the laser scanning velocities at 10~1000 mm/s underline width about 0.96 μm~1.07 μm. The experiment results confirm that the laser apparatus is effective when applied to a stainless steel CIGS solar cell P2 layer.